UJI AKTIVITAS ANTIBAKTERI EKSTRAK DAUN TABAT BARITO (Ficus deltoidea) TERHADAP BAKTERI Bacillus substillis DENGAN TINGKATAN POLARITAS PELARUT - Rahayu, Sri; Amaliah, Noor; Patimah, Raudatul (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2022)
Tabat barito leaf (Ficus deltoidea) is a single leaf of a sole form, the leaf has round tip with a flat edge and a pointed base. These leaves have a smooth surface, coloured green above and brownish yellow beneath. This study aims to determine the antibacterial activity of polar, semi-polar and non-polar compounds contained in Tabat barito leaf extract extracted with solvents of different polarity. The highest bacterial inhibition was also measured against Bacillus substillis which is a gram-positive bacterial. The maceration method uses 3 levels of solvents with different polarities, started with a non-polar solvent (n-hexan), a semi-polar solvent (ethyl acetate) and finally macerated with a polar solvent (methanol). The bacterial activity test was done with diffusion method. The results showed that the Tabat Barito leaf extract contained antibacterial compounds that were non-polar, semi-polar and polar. The highest inhibition of the hexane extract at concentration 15% with a clear zone diameter of 22.33 mm in very strong inhibition category against Bacillus substilis bacteria